Percepção ambiental e sustentabilidade: um estudo com educadores da rede pública de ensino de Itaporanga d'Ajuda//SE - Franco, Juciara Torres (2009)
This study aims to examine the perceptions of teachers of environmental public school system (municipal and state) of Itaporanga d‟Ajuda/SE, participants of the I Training Course for multipliers in Environmental Education and Environmental Education and the contribution to the sustainability of the Environmental Reserve of the agroecosystems and the conservation unit. The I Course of Training Multipliers in Environmental Education was organized in seven (7) modules that occurred on Thursdays, in full time, between the months March and May of 2008. The campaigns of field occurred from April to July of 2008, with the application of semi-structured in a predominantly qualitative approach, applied to 28 teachers of elementary and high school, between men and women with different age groups, which were participants I Course Training of Multipliers in Environmental Education. The methodology used was the participant observation, which had as objective recording and analyzing the discourse of teachers during the course of conducting various phases of the training course, characterizing them according to the current environmental awareness and the environment. The search showed the concern of teachers of the course with environmental issues, however, observed that in general the perception of teachers is limited, that occur for factors as: lack of reading teachers, deficient training, lack of training and skills that contribute to the continuing education of teachers. Thus, it is emphasized that the agroecosystems are defined this study on the scale of owned by the Environmental Reserve and in the establishments in this environment.